Initiation of Infection by Deoxyribonucleic Acid From Bacteriophage λ - Elseth, Gerald D. (J Bacteriol, 1967)
Kinetic studies conducted on the early stages of infection of Escherichia coli K-12 by deoxyribonucleic acid (DNA) isolated from bacteriophage λ indicate a rapid adsorption of the phage DNA to receptor sites at the bacterial surface prior to deoxyribonuclease-insensitive incorporation. A direct relationship found between the number of DNA molecules adsorbed per bacterium and the multiplicity of helper phage infection indicates a requirement for helper function during the attachment process. An apparent lack of attachment specificity with regard to the source of the DNA preparation, to the size of the inhibiting fragment, to the base ratio of the inhibiting DNA molecule, and to “cohesive” ends suggests a nonspecific interaction between the infectious DNA and the sites of helper phage attachment.